A closed-form hydraulic-mechanical coupling solution of a circular tunnel in elastic-brittle-plastic rock mass. Issue 8 (11th June 2022) - Zhang, Qiang; Shao, Cong; Su, Haijian; Wang, Hongying; Jiang, Yujing; Jiang, Binsong
Abstract: Considering the changes of permeability and Biot's coefficients, the closed-form elastic-brittle-plastic solution of lined circular tunnels was proposed employing a Mohr-Coulomb non-associated flow rule. The influence of the reserved deformation of lining structure, permeability and Biot's coefficients on the plastic radius, displacement and water inflow was studied. With an increase in permeability of the plastic region, the plastic radius and displacement decrease, and the water inflow increases. With an increase in Biot's coefficient, the plastic radius, displacement and water inflow approximately increase in a linear way. The pore-water pressure in the surrounding rock increases with decreasing permeability of lining structure, and the water inflow has a contrary evolution. The increasing reversed displacement of lining structure increases the plastic radius, and lining structure reduces the water inflow but increases the pore-water pressure of the surrounding rock.